Association between polymorphisms in the aryl hydrocarbon receptor repressor gene and disseminated testicular germ cell cancer - Brokken, Leon J.; Lundberg-Giwercman, Yvonne; Rajpert-De Meyts, Ewa; Eberhard, Jakob; Stahl, Olof; Cohn-Cedermark, Gabriella; Daugaard, Gedske; Arver, Stefan; Giwercman, Aleksander (Frontiers in Endocrinology, 2013)
In the Western world, testicular germ cell cancer (TGCC) is the most common malignancy of young men. The malignant transformation of germ cells is thought to be caused by developmental and hormonal disturbances, probably related to environmental and lifestyle factors because of rapidly increasing incidence of TGCC in some countries. Additionally, there is a strong genetic component that affects susceptibility. However, genetic polymorphisms that have been identified so far only partially explain the risk of TGCC. Many of the persistent environmental pollutants act through the aryl hydrocarbon receptor (AHR). AHR signalling pathway is known to interfere with reproductive hormone signalling, which is supposed to play a role in the pathogenesis and invasive progression of TGCC. The aim of the present study was to identify whether AHR-related polymorphisms were associated with risk as well as histological and clinical features of TGCC in 367 patients and 537 controls. Haplotype-tagging single nucleotide polymorphisms (SNPs) were genotyped in genes encoding AHR and AHR repressor (AHRR). Binary logistic regression was used to calculate the risk of TGCC, nonseminoma versus seminoma, and metastasis versus localised disease. Four SNPs in AHRR demonstrated a significant allele association with risk to develop metastases (rs2466287: OR = 0.43, 95% CI 0.21-0.90; rs2672725: OR = 0.49, 95% CI: 0.25-0.94; rs6879758: OR = 0.27, 95% CI: 0.08-0.92; rs6896163: OR = 0.34, 95% CI: 0.12-0.98). This finding supports the hypothesis that compounds acting through AHR may play a role in the invasive progression of TGCC, either directly or through modification of reproductive hormone action.